Mala karşı işlenen suçlarda indirim nedeni olarak ihkak-ı hak - Çetin, Muharrem (My University, 2006)
MALA KARŞI İŞLENEN SUÇLARDA İNDİRİM NEDENİ OLARAK İHKAK-I HAK Muharrem Cetin ÖZET Kısaca kendi hakkını alma olarak tarif edebileceğimiz ihkakı hak, 5237 sayılı TCK’da önceki 765 sayılı TCK’dan farklı olarak müstakil bir suç olarak düzenlenmemiştir. 5237 sayılı TCK’da bu durum sadece hırsızlık, yağma ve dolandırıcılık suçlarında indirim nedeni olarak kabul edilmiştir. Yani bir hukuki ilişkiye dayanan alacağın tahsili amacıyla bu (hırsızlık, yağma ve dolandırıcılık)suçlar işlendiğinde suçun failine daha az ceza verilecektir. Bu düzenlemedeki temel hareket noktası bu suçu işleyen failin (amacı) saikidir. Ayrıca adalet ve hakkaniyet düşüncesi de bu düzenlemeyi gerektirmektedir. Kanunda, bir huhuki ilişkiye dayanan alacağın tahsili amacıyla hırsızlık ve dolandırıcılık suçlarını işleyen fail için ceza süresi de belirtilmek suretiyle müstakil bir ceza öngörüldüğü halde, yağma suçunda durum özellik arzetmektedir. Şöyleki; fail bir hukuki ilişkiye dayanan alacağın tahsili amacıyla kanunda tarif olunan yağma suçunu işlediğinde, suçun işleniş şekline göre faile kasten yaralama ve/ veya tehdit suçlarından ceza verilecektir. İhkakı hak durumunun ceza kanununda müstakil bir suç olarak düzenlenmesi(765 sayılı TCK’da olduğu gibi) daha yerinde olacaktır. 5237 sayılı TCK düzenlemesinde de suç failindeki saik bazı suçlar için dahi olsa hukukun genel ilkeleri çerçevesinde kanun koyucuyu cezada indirim yapmaya zorlamıştır. RETAKING OF ONE’S RIGHT BY SELF-HELP AS A COMMUTATIVE ELEMENT IN THE CRIMES AGAINST PROPERTY Muharrem Cetin

Generally a person may assert a “claim of right” to possession of property or of the title and, therefore, seek to dispossess another of the disputed property or of any title which is, by definition, called retaking of one’s right by self-help. This situation was placed in the previous Criminal Code of Turkey, the law no. 765, as an independent offense governed by Article 308 of the Code. However, the previous Code has been replaced by the new Code, the law no. 5237; and the new Code has modified the “claim of right” situation in the criminal law completely. The new Code does not make the “claim of right” an independent offense, but it still recognizes the claim of right situation as a commutative element in the determination of criminal liability for specifically such crimes as theft, robbery and fraudulent, which means that when the said crimes committed with a specific intent (motive) to retake her right of which she has bee deprived, and her right to money owed to her (or credit) which has been based on a legal relationship recognized by the legal order, this specific mental state shall be a commutative element in the establishment of the criminal responsibility for the consequent offenses such as theft, robbery and fraudulent. The idea of justice and rightfulness requires that the defendant be punished less if she had such motive while performing the unlawful act. The situation of “claim of right” is of special importance in the case of committing robbery with a motive to retake her money owed to her, the money based on a legal relationship. In this case, the act may result -according to the way in which the act is performed- in either assault, battery, mayhem or threat offenses. The situation of “claim of right” should have been placed in the Code as an independent offense as was in the previous Code. However, the lawmaker must have felt in need to commutate the liability in the commission of the said crimes when the actor had the claim of right intent or motive. Otherwise, it would be contrary to the general principles of criminal law, to the basic principles of criminal responsibility.
Keywords: İhkak-ı Hak Suçu